AN ANALYTICAL STUDY OF THE VARIOUS HOME ECONOMICS EDUCATION CURRICULA IN SELECTED LAND-GRANT COLLEGES OF THE NORTH ATLANTIC REGION ... - Spencer, Mabel Sidell (ProQuest, 2023)
Source: Dissertation Abstracts International, Volume: 20-10, page: 4045. ...